Analysis of factors influencing formwork material selection in construction buildings. (2021) - Rajeshkumar, V.; Anandaraj, S.; Kavinkumar, V.; Elango, K.S.
Abstract: Formwork material selection is a crucial factor for the successful completion of the project. Selection of the right formwork material is essential for faster construction and improved productivity. The study reports the factors influencing the selection of different formwork material in the construction of high rise buildings through structural questionnaire survey from the client, contractor, consultant, and interviews with expert members. Total of 40 technical factors was identified from the literature and 220 filled questionnaires were received from the respondent in the state of Tamilnadu in India. The top ten factors identified as having a significant impact on formwork material selection are the accessibility to work, quality, surface finish, storage of formwork, capital cost, safety, layout of structures, lifespan, exposure to environment and labor cost. Additionally, from factor analysis 22 factors were identified to have a correlation with one another and the remaining 18 factors excluded since they do not have a correlation with other factors. The findings provide a better understanding of the factors influencing formwork selection in the Indian context and will aid construction practitioners in making effective plans and increase the existing knowledge in relation to formwork material selection and can reduce the formwork waste.